The good shepherd - Gunnarsson, Gunnar frey50 (Indianapolis Bobbs-Merrill, 1940)
A simple, beautiful, gripping and moving tale of an Icelandic shepherd, maing his twenty-seventh annual journey into the bleak and stormy wastes of the mountais to rescue the sheep that have been missed in the yearly ingathering. With his two comrades, Leo, the dog, and Gnarly, the wether, he preforms feats of endurance, patience and presistence that are nobly heroic. Yet he does it all without heroics - just as a mater-of-course duty to the dumb animals and to his neighbors.
Keywords: Christmas stories